Prospective cholestanol screening of cerebrotendinous xanthomatosis among patients with juvenile-onset unexplained bilateral cataracts - Gorka Fernández-Eulate; Gilles C. Martin; Pascal Dureau; Claude Speeg-Spatz; Anais Brassier; Perrine Gillard; Dominique Bremond-Gignac; Dominique Thouvenin; Cecile Pagan; Foudil Lamari; Yann Nadjar (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Cerebrotendinous xanthomatosis (CTX) is a rare genetic disorder related to CYP27A1 biallelic mutations, leading to decreased synthesis of bile acids and increased cholestanol. Juvenile bilateral cataracts are one of the most common findings in the disease, frequently occurring before the onset of neurological manifestations. While early treatment with chenodeoxycholic acid can prevent the onset of neurological impairment, poor awareness of CTX accounts for a markedly delayed diagnosis. The objective of this study was to evaluate the utility of plasma cholestanol analysis at the moment of cataract diagnosis and before the onset of neurological impairment in CTX. Methods Multicenter prospective cohort study of patients with juvenile-onset unexplained bilateral cataracts recruited from seven French ophthalmology departments. Plasma cholestanol analysis was performed at diagnosis from January 2018 to January 2020. CYP27A1 genetic testing was performed at the ophthalmologist’s discretion. Cholestanol levels were compared with those of a similar population of patients without cataracts (control cohort). Results 30 patients were finally recruited, with a mean age at cataract diagnosis of 7.1 years (± 4.8 SD, range 1–19 years). One patient had a very high cholestanol level (68 μmol/L, reference < 10) and carried two pathogenic heterozygous mutations in CYP27A1 confirming CTX. This patient was a 19-year-old female, reporting chronic diarrhea only in childhood, and diagnosed with bilateral posterior cataracts with cortical fleck-like opacities. Therefore, the incidence of CTX in our cohort of patients was 3.3%. Five further patients (5/29; 17.2%) had moderate elevations of cholestanol level (between 10.3 and 16.5 μmol/L), compared to 12/286 (4.2%) in the control cohort (p = 0.014) after adjustment for age. Conclusion Our study argue for the relevance of plasma cholestanol CTX screening in all patients with juvenile-onset unexplained cataracts, even without other CTX identified manifestations. Whether moderate elevations of plasma cholestanol unrelated to CTX may be a risk factor for bilateral cataracts occurrence needs further examination.